Predictors for failure of early neurological improvement after successful thrombectomy in the anterior circulation - Weyland, Charlotte S.; Mokli, Yahia; Vey, Johannes; Kieser, Meinhard; Herweh, Christian; Schönenberger, Silvia; Bendszus, Martin; Möhlenbruch, Markus Alfred; Ringleb, Peter A.; Nagel, Simon (Stroke, 2021)
Background and Purpose:Failure of early neurological improvement (fENI) despite successful mechanical thrombectomy in the anterior circulation is a clinically frequent occurrence. Purpose of this analysis was to define independent clinical, radiological, laboratory, or procedural predictors for fENI.Methods:Retrospective single-center analysis of patients treated for acute ischemic stroke in the anterior circulation ensuing successful mechanical thrombectomy between January 2014 and April 2019. Patients were compared according to fENI (equal or higher National Institutes of Health Stroke Scale) and ENI (lower National Institutes of Health Stroke Scale at discharge). Thirty-eight variables were examined in multivariable analysis for association with fENI.Results:Five hundred forty-nine out of 1146 patients experienced successful recanalization (modified Treatment in Cerebral Ischemia 2c-3). fENI occurred in 115/549 (20.9%) patients. Independent predictors of fENI were premorbid modified Rankin Scale (odds ratio [OR] per point [IC], 1.21 [1.00-1.46], P=0.049), end-stage renal failure (OR [IC], 12.18 [2.01-73.63], P=0.007), admission glucose (OR [IC], 1.018 [1.004-1.013] per mg/dL, P=0.001), bridging IV lysis (OR [IC], 0.57 [0.35-0.93], P: 0.024), time from groin puncture to final recanalization (OR [IC], 1.004 [1.001-1.007] per minute, P=0.015), general anesthesia during mechanical thrombectomy (OR, 2.41 [1.43-4.08], P<0.001), symptomatic intracranial hemorrhage (OR [CI], 6.81 [1.84-25.16], P=0.004), and follow-up Alberta Stroke Program Early CT Score (OR [IC], 0.76 [0.69-0.84] per point, P<0.001). In a secondary analysis, involvement of the regions internal capsule, M4 and M5 (motor cortex) were further independent predictors for fENI. Patients with ENI were more likely to experience a good outcome (modified Rankin Scale on day 90, 0-2: n=229/435 [52.8%] versus n=13/115 [11.3%]; P<0.001).Conclusions:The extent of infarction and the involvement of motor cortex and internal capsule as well as higher premorbid modified Rankin Scale, end-stage renal failure, high glucose level on admission, absence of bridging IV lysis, general anesthesia, and a longer therapy interval are presumably independent predictors for fENI in patients with successful mechanical thrombectomy.